2016
DOI: 10.1007/s12560-016-9247-3
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Enteric Viruses by Blueberry Juice and Blueberry Proanthocyanidins

Abstract: Blueberry and blueberry extracts are known for their health benefits and antimicrobial properties. Natural therapeutic or preventive options to decrease the incidences of foodborne viral illnesses are becoming popular and being researched. This study aimed to determine the antiviral effects of blueberry juice (BJ) and blueberry proanthocyanidins (BB-PAC, B-type PAC structurally different from A-type PAC found in cranberries) against the infectivity of hepatitis A virus (HAV) and human norovirus surrogates (fel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 41 publications
2
42
0
2
Order By: Relevance
“…Monomeric catechin hydrate at 1 mg/mL was shown to reduce FCV-F9 titers to undetectable levels after 6 h, while increased concentration of 5 mg/mL monomeric catechin hydrate reduced FCV-F9 titers to nondetectable levels within a shorter time of 1 h ( Table 1). The dimeric Btype procyanidin, PB2 at lower concentrations of 0.5 and 1 mg/mL was shown to reduce FCV-F9 titers to undetectable levels after 3 h. In comparison, earlier studies showed that blueberry procyanidins (B-PACs, 0.5 mg/mL) and cranberry procyanidins (C-PACs, 1.2 mg/mL) could reduce FCV-F9 titers to undetectable within 1 h at 37°C (Joshi et al, 2016;Su et al, 2010a,b).…”
Section: Comparison Of Antiviral Activity Of Monomeric and Polymeric mentioning
confidence: 75%
See 4 more Smart Citations
“…Monomeric catechin hydrate at 1 mg/mL was shown to reduce FCV-F9 titers to undetectable levels after 6 h, while increased concentration of 5 mg/mL monomeric catechin hydrate reduced FCV-F9 titers to nondetectable levels within a shorter time of 1 h ( Table 1). The dimeric Btype procyanidin, PB2 at lower concentrations of 0.5 and 1 mg/mL was shown to reduce FCV-F9 titers to undetectable levels after 3 h. In comparison, earlier studies showed that blueberry procyanidins (B-PACs, 0.5 mg/mL) and cranberry procyanidins (C-PACs, 1.2 mg/mL) could reduce FCV-F9 titers to undetectable within 1 h at 37°C (Joshi et al, 2016;Su et al, 2010a,b).…”
Section: Comparison Of Antiviral Activity Of Monomeric and Polymeric mentioning
confidence: 75%
“…(Table 2). In comparison, B-PAC at 1 mg/mL was shown to reduce MNV-1 titers to undetectable after 3 h of treatment at 37°C (Joshi et al, 2016), while 0.5 mg/mL C-PAC reduced MNV-1 titers to undetectable after 6 h of treatment at 37°C (Su et al, 2010b).…”
Section: Comparison Of Antiviral Activity Of Monomeric and Polymeric mentioning
confidence: 85%
See 3 more Smart Citations